COMPETENCES DEVELOPMENT PROCESS RECORDING FOR MULTI-COMPETENCE E-COURSE - Gorbunovs, Aleksandrs; Kapenieks, Atis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Understanding of students’ current level of competencies might be tailored with a finding of the challenging learning approaches to strengthen and enhance their own competencies, and obtain the new ones. Learning paths, which are usually offered by educational organizations to students, as often as not prescribe monotonous acquiring of knowledge. Making a study course more interactive, there are appearing additional features like working in ePortfolio environment which noticeably influence competences level. This paper provides an overview of research results in competences development process recording for multi-competence e-course, assessing competences level of students, both at initial and on-going stages, and analysis of competences interrelation within particular subject domain, e.g. basic business course, as well as an impact of the study themes on different competencies.